2016
DOI: 10.5935/0034-7140.20160011
|View full text |Cite
|
Sign up to set email alerts
|

Compromisso fiscal, expectativas empresariais e produção industrial: o caso brasileiro

Abstract: Este trabalho analisa os efeitos do comprometimento fiscal sobre a confiança dos empresários e como esta impacta as decisões de produção. O estudo contribui com a literatura, pois é o primeiro a abordar a influência da reputação fiscal e do alcance das metas de superávit primário sobre a confiança dos empresários. Os achados apontam que o desenvolvimento da reputação fiscal e o cumprimento das metas de superávit primário sinalizam aos empresários um maior comprometimento do governo com as contas públicas, o qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In an analysis of the business confidence in Brazil, Montes (2013), Montes and Bastos (2013) and de Mendonça and Almeida (2018) find evidence that the main macroeconomic variables, and in particular the monetary policy credibility, are able to influence the business confidence. The work of Montes and Almeida (2016) indicates that business confidence of industrial entrepreneurs is a relevant expectation channel through which fiscal commitment affects industrial production. Montes and Almeida (2017), analyzing the effect of corruption on business confidence for a set of 40 countries, reveal the adverse impact that corruption perception has on business confidence.…”
Section: Business Confidence and Crimementioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of the business confidence in Brazil, Montes (2013), Montes and Bastos (2013) and de Mendonça and Almeida (2018) find evidence that the main macroeconomic variables, and in particular the monetary policy credibility, are able to influence the business confidence. The work of Montes and Almeida (2016) indicates that business confidence of industrial entrepreneurs is a relevant expectation channel through which fiscal commitment affects industrial production. Montes and Almeida (2017), analyzing the effect of corruption on business confidence for a set of 40 countries, reveal the adverse impact that corruption perception has on business confidence.…”
Section: Business Confidence and Crimementioning
confidence: 99%
“…Therefore, since confidence and expectations affect production and investment decisions, business confidence is widely considered as a transmission mechanism of the expectation channel through which economic and noneconomic variables influence economic activity. Studies have found evidence that the main macroeconomic variables (Ferreira et al, 2008;Konstantinou and Tagkalakis, 2011;Khumalo, 2014;Martinez-Serna and Navarro, 2015), fiscal policy (Konstantinou and Tagkalakis, 2011;Montes and Almeida, 2016), monetary policy (Montes, 2013;Montes and Bastos, 2013;de Mendonça and Almeida, 2019), corruption (Montes and Almeida, 2017) and terrorism (Drakos and Kalandranis, 2015) affect the economy through business confidence.…”
Section: Business Confidence and Crimementioning
confidence: 99%